UPAYA MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN DENGAN PENERAPAN METODE READING ALOUD BERBANTUAN FLASHCARD - Maya Sari; Ratu Dinny Fauziah (Jurnal Cendekia Ihya, 2023)
This study aims to improve the beginning reading skills of grade 1 students of SDIT Al Yasmin 2 Bogor through the application of the Reading Aloud method with flashcard media. This method has been proven effective in improving children's beginning reading skills. The research was conducted in two cycles involving 13 students. The results showed a significant improvement in students' beginning reading skills after applying the Reading Aloud method with flashcards media. Learning activities with this method increased students' interest and motivation in reading, expanded vocabulary, and improved text comprehension. The recommendation of this study is to adopt the Reading Aloud method with flashcards media in learning beginning reading in grade 1.